Educational Intervention on Splinting Management and First Aid for Snake Bites in Gunungsari Tourism Village, Boja - Satriya Pranata; Aric Vranada; Adzan Raihandasyarif Darmawan; Nurul Afiana Salsabilla; Novita Andaresta Putri; Risnatun Hasanah (Journal of Health Community Service, 2024)
Gunungsari Village, renowned for its camping and natural tourism attractions nestled amidst mountains and rivers, faces potential hazards such as snake bites and fractures resulting from falls. Prompt and appropriate first aid and treatment are crucial in mitigating the risks associated with these incidents. However, there is a notable gap in public knowledge regarding snake bite management and the availability of antivenom, which can exacerbate mortality rates. In response, the community service team from Faculty of Nursing and Health Sciences, The University of Muhammadiyah Semarang initiated a training program aimed at educating locals about snake bite management and splinting techniques. Fifteen participants, comprising members of the disaster management agency team in the Boja area, engaged in the training sessions. While possessing foundational knowledge, participants acknowledged the novelty and importance of information regarding snake venom management. Pre-training assessments revealed an average knowledge score of 68, which significantly increased to 84 post-training, indicating a substantial improvement in understanding. Additionally, simulation exercises assessing splint application demonstrated commendable proficiency among participants, with an average score of 82. The training initiative underscores the significance of enhancing community preparedness in managing medical emergencies such as snake bites and fractures. The newfound knowledge and skills acquired through the training sessions equip participants with the ability to administer timely and effective first aid in emergency situations. Continuous training efforts are recommended to sustain and further enhance the preparedness of Gunungsari Village residents in addressing medical emergencies in the future.